2020
DOI: 10.21203/rs.3.rs-25856/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting furin activity through in silico and in vitro drug repurposing strategy for SARS-CoV-2 spike glycoprotein cleavage repression

Abstract: In December 2019, a new coronavirus was identified in the Hubei province of central china and named SRAS-CoV-2. This new virus induces COVID-19, a severe respiratory disease with high death rate. The spike protein (S) of SARS-CoV-2 contains furin-like cleavage sites absent the other SARS-like viruses. The viral infection requires the priming or cleavage of the S protein and such processing seems essential for virus entry into the host cells. Furin is highly expressed in the lung tissue and the expression is fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The results of our study confirmed that punicalin and punicalagin interacted with furin active site amino acid residues forming more stable complexes than sulconazole as a positive control. Sulconazole, a broad-spectrum anti-fungal agent, was found to be the most promising candidate with anti-furin activity from the collection of about 8000 molecules [53]. Contrary to the less significant results of binding energies achieved in docking analysis with the S glycoprotein and ACE2, ellagic and gallic acids formed stable complexes with furin revealing binding energies to be −7.801 and − 7.486 kcal/mol, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…The results of our study confirmed that punicalin and punicalagin interacted with furin active site amino acid residues forming more stable complexes than sulconazole as a positive control. Sulconazole, a broad-spectrum anti-fungal agent, was found to be the most promising candidate with anti-furin activity from the collection of about 8000 molecules [53]. Contrary to the less significant results of binding energies achieved in docking analysis with the S glycoprotein and ACE2, ellagic and gallic acids formed stable complexes with furin revealing binding energies to be −7.801 and − 7.486 kcal/mol, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…[19][20][21][22] Even though surface modified PAMAM dendrimers were studied as antiviral agents, 23,24 molecular modelling studies of the PAMAM dendrimer with biological targets have received meagre attention, not to mention the gap in correlating the computational studies and experimental results. 25 Similarly, very few reports have attempted the in silico screening of novel molecules for furin inhibition, 26,27 specifically to understand the molecular level interactions at the catalytic site. Hence, we envisaged the design of a library of molecular conjugates comprising PAMAM and GTU units and explored their interactions within furin's catalytic pockets to decipher mechanistic insights and provide molecular level analysis of the resulting interactions.…”
Section: Introductionmentioning
confidence: 99%